Should death penalty be upheld as a capital punishment in Malaysia? / Norfadzly Jamaluddin, Muhammad Nud'man Yang Omar and Mohd Raimi Mohd Zaini - Jamaluddin, Norfadzly; Muhammad Nud'man, Yang Omar; Mohd Zaini, Mohd Raimi (2005)
Capital punishment, also known as the death penalty, is the execution of a convicted felon as a punishment for a crime. At one time the death penalty was used in almost every part of the world but over the last few decades many countries have abolished it. In Malaysia the issue of death penalty has come up recently.The main focus of this study is to determine whether death penalty is justified in Malaysia. It also looks, albeit briefly into religious point of view on death penalty such as Christianity, Hinduism, and especially Islamic point of view which is official religion of Malaysia. This study discussed on why the death penalty should be upheld and why death penalty should be abolish in Malaysia. The pro and contrast of death penalty. This study will contribute to the reader by giving them knowledge on capital punishment or death penalty. This study also contains recommendations on the issue. Hopefully, this research will enlighten the public or readers in Malaysia regarding death penalty.